Modified electro-optical modulator based bipolar optical code division multiple access for free-space optics - Eddy Wijanto; Kevin Sutanto (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2025)
This study introduces a modified electro-optical modulator (EOM) to enhance bipolar optical code division multiple access (OCDMA) in free-space optical (FSO) communication. The proposed system improves signal quality, spectral efficiency, and resilience to atmospheric turbulence. Unlike conventional dual EOM techniques, the modified EOM enables simultaneous transmission of ‘0’ and ‘1’ chip values, reducing multiple access interference (MAI) and enhancing system robustness. This approach optimizes bandwidth utilization and ensures stable performance in varying environmental conditions. Simulations were conducted in an additive white Gaussian noise (AWGN) channel using three spectral amplitude coding (SAC) schemes: modified M sequence, Walsh-Hadamard, and random diagonal (RD) codes. Results indicate that the modified EOM scheme significantly improves FSO system performance, achieving an average 47.1% lower minimum log of bit error rate (BER) in normal weather and 43.3% lower in extreme weather, ensuring superior noise suppression and signal integrity across varying environmental conditions. Additionally, the system maintains superior performance over longer distances, demonstrating its suitability for high-speed, long-range FSO applications. These findings highlight the potential of the modified EOM based bipolar OCDMA system in advancing next-generation optical wireless networks, offering a more efficient, interference-resistant, and high-capacity communication solution for future technologies such as 6G and beyond.